ANALISIS KELAYAKAN FINANSIAL USAHATANI BELIMBING DI KABUPATEN MUSI RAWAS (JASEP, 2021)
Starfruit has become one of new sourch of economic growth in rural area. One of starfruit farming can be found atTugumulyo District Musi Rawas Regency. The production of starfruit farming at Tugumulyo in 2018 reach value at 429 kuintal from 214 starfruit tree. The purpose of this research was analize the finansial feasibility of starfruit farming at Tugumulyo District Musi Rawas Regency. This research methode was cases study with location choosen purposively. Based on this research we know that starfruit farming feasible with NVP at 862.125.159, IRR 25 % B/C 4,83, and payback periode 4,07. Keyword: farming, feasibility study, starfruit